Pridopidine for the Improvement of Motor Function in Patients With Huntington's Disease: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Chen, Shujun; Liang, Tianyu; Xue, Tao; Xue, Shouru; Xue, Qun (Frontiers in Neurology, 2021)
Background: Huntington's disease (HD) is a progressive neurodegenerative disorder. Generally, it is characterized by deficits in cognition, behavior, and movement. Recent studies have shown that pridopidine is a potential and effective drug candidate for the treatment of HD. In the present study, we performed a meta-analysis to evaluate the efficacy and safety of pridopidine in HD. Methods: The MEDLINE, EMBASE, CENTRAL, and Clinicaltrials.gov databases were searched for randomized controlled trials (RCTs) which had that evaluated pridopidine therapy in HD patients. Results: We pooled data from 1,119 patients across four RCTs. Patients in the pridopidine group had a significantly lower Unified Huntington's Disease Rating Scale (UHDRS)-modified Motor Score (mMS) (MD −0.79, 95% CI = −1.46 to −0.11, p = 0.02) than those in the placebo group. Additionally, no differences were observed in the UHDRS-Total Motor Score (TMS) (MD −0.91. 95% CI = −2.03 to 0.21, p = 0.11) or adverse events (RR 1.06, 95% CI = 0.96 to 1.16, p = 0.24) in the pridopidine and placebo groups. In the subgroup analysis, the short-term (≤12 weeks) and long-term (>12 weeks) subgroups exhibited similar efficacy and safety with no statistical significance in TMS, mMS, or adverse events. However, TMS (MD −1.50, 95% CI = −2.87 to −0.12, p = 0.03) and mMS (MD −1.03, 95% CI = −1.87 to −0.19, p = 0.02) were observed to be improved significantly when the dosage of pridopidine ≥90 mg/day. Additionally, pridopidine (≥90 mg/day) increased total adverse events (RR 1.11, 95% CI = 1.00 to 1.22, p = 0.04) compared with placebo. On this basis, we analyzed the incidence of various adverse events when the dosage was ≥90 mg/day. Nonetheless, these results were within the acceptable threshold, although patients developed symptoms, such as nasopharyngitis and insomnia. Conclusion: Pridopidine improved mMS and had no statistical significance in association with TMS or adverse events. Pridopidine (≥90 mg/day) improved TMS and mMS but increased adverse events, such as nasopharyngitis and insomnia. More RCTs were expected to assess pridopidine in HD.